Establishing Propagation Nodes as a Basis for Preventing Large Wildfires: The Proposed Methodology - Quílez, Raúl; Valbuena, Luz; Vendrell, Jordi; Uytewaal, Kathleen; Ramirez, Joaquín (Frontiers in Forests and Global Change, 2020)
The challenge presented by wildfires is amplified due to socioeconomic changes in the last 40 years and inadequate land management in the context of climate change. In Spain, wildfire prevention is commonly understood as a collection of actions performed in the territory that serves to support fire suppression in order to mitigate the effects of fire on forest tracts and human activity (i.e. modifying fuel models, access to forest areas, water sources for extinguishing purposes, or surveillance infrastructures of the territory). These practices stem from a classical vision of management. Often fire prevention infrastructure is limited to creating or maintaining previous firebreaks without assessing their functionality according to the behavior of the current fire. When facing large wildfires, the political and technical strategies are fundamentally based on favoring all types and technologies for suppression, without considering extreme fire behavior or the true utility of these technologies compared with their cost. The current work proposes an operational methodology that reduces the particular uncertainty associated with the suppression of large wildfires. In order to reduce uncertainty, it is necessary to address the scientific and technical knowledge gained from past large fires in the area, supported by new simulation technologies and GIS analysis. The method determines where large fires may propagate in the future; that is, to locate “propagation nodes” within the territory. This analysis gives rise to feasibly determining the most suitable areas for wildfire preventative action, which is essential in order to estimate the effects of high intensity fires.